Method of isolating humic acid. - Ahmed, Osumanu Haruna; Kasim, Susilawati; Nik Ab. Majid, Nik Muhamad (2009)
The present invention is a simple, rapid and cost-effective ,method of isolating humic acids from organic and inorganic materials. The method comprises the steps of: (a) dissolving a humic acid containing substance in an alkaline solution; (b) subjecting the mixture of humic acid containing substance and alkaline solution to centrifugation to obtain a supernatant layer as a precipitate layer; (c) reacting the precipitate layer with an acidic solution to obtain a suspension layer containing humic acid; (d) subjecting the suspension layer containing humic acid to centrifugation to obtain a precipitate; (e) washing the precipitate with distilled water, thus obtaining a purified humic acid extract.